Epigenetic silencing of tumor suppressor miR-3151 contributes to Chinese chronic lymphocytic leukemia by constitutive activation of MADD/ERK and PIK3R2/AKT signaling pathways - Wang, Lu Qian (Oncotarget, 2015)
We hypothesize that miR-3151, localized to a GWAS-identified chronic lymphocytic leukemia (CLL) risk locus (8q22.3), is a tumor suppressor miRNA silenced by promoter DNA methylation in CLL. The promoter of miR-3151 was methylated in 5/7 (71%) CLL cell lines, 30/98 (31%) diagnostic primary samples, but not normal controls. Methylation of miR-3151 correlated inversely with expression. Treatment with 5-Aza-2′-deoxycytidine led to promoter demethylation and miR-3151 re-expression. Luciferase assay confirmed MAP-kinase activating death domain (MADD) and phosphoinositide-3-kinase, regulatory subunit 2 (PIK3R2) as direct targets of miR-3151. Moreover, restoration of miR-3151 resulted in inhibition of cellular proliferation and enhanced apoptosis, repression of MADD and PIK3R2, downregulation of MEK/ERK and PI3K/AKT signaling, and repression of MCL1. Lastly, miR-3151 methylation was significantly associated with methylation of miR-203 and miR-34b/c in primary CLL samples. Therefore, this study showed that miR-3151 is a tumor suppressive miRNA frequently hypermethylated and hence silenced in CLL. miR-3151 silencing by DNA methylation protected CLL cells from apoptosis through over-expression of its direct targets MADD and PIK3R2, hence constitutive activation of MEK/ERK and PI3K/AKT signaling respectively, and consequently over-expression of MCL1.